2019
DOI: 10.1515/cclm-2019-0214
|View full text |Cite
|
Sign up to set email alerts
|

Pre-analytical practices for routine coagulation tests in European laboratories. A collaborative study from the European Organisation for External Quality Assurance Providers in Laboratory Medicine (EQALM)

Abstract: Background Correct handling and storage of blood samples for coagulation tests are important to assure correct diagnosis and monitoring. The aim of this study was to assess the pre-analytical practices for routine coagulation testing in European laboratories. Methods In 2013–2014, European laboratories were invited to fill in a questionnaire addressing pre-analytical requirements regarding tube fill volume, citrate concentration, sample stability, centrifugation and storage conditions for routine coagulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…An estimated 27% of D‐Dimer requests in UHL are tested subsequently requested by a clinician following referral of the initial coagulation screen. In a recent survey, over half of laboratory centres (56%) used plasma from centrifuged primary coagulation containers for add‐on tests 10 . Previous studies have examined the effect of refrigeration on coagulation plasma aliquots 2,11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An estimated 27% of D‐Dimer requests in UHL are tested subsequently requested by a clinician following referral of the initial coagulation screen. In a recent survey, over half of laboratory centres (56%) used plasma from centrifuged primary coagulation containers for add‐on tests 10 . Previous studies have examined the effect of refrigeration on coagulation plasma aliquots 2,11 .…”
Section: Discussionmentioning
confidence: 99%
“…In a recent survey, over half of laboratory centres (56%) used plasma from centrifuged primary coagulation containers for add-on tests. 10 Previous studies have examined the effect of refrigeration on coagulation plasma aliquots. 2,11 However, the practice of aliquoting plasma from centrifuged primary coagulation containers for potential subsequent add-ons can be difficult to implement in some laboratories due to time, financial and space constraints.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure the right sample transportation, local requirements have to be defined and distributed to all clinicians, nursing staff and carriers (22,59). A survey among European laboratories on preanalytical practices for coagulation tests recently found that only 42% of participating laboratories are actually monitoring temperature during transportation (60). Reported proportions of unsuitable samples due to inappropriate time and temperature condi-tions can be as high as 3.4% and 1.2% of all samples received (Figure 5), respectively, and 1.9% in relation to the errors analysed (Figure 4) (7,44).…”
Section: Transportmentioning
confidence: 99%
“…Since recommendations on centrifugation conditions from manufacturers of blood collection systems as well as other sources differ in time and speed, ranging from ≤ 1300xg to 4000xg, and from 3 to 15 minutes ), this preanalytical step may display large heterogeneity (58,(73)(74)(75). A survey carried out by the External Quality Assurance Providers in Laboratory Medicine (EQALM) recently confirmed that this practice is considerably variable across many European laboratories (60). Since blood tubes manufacturers cannot validate all available parameters on all analytical platforms, recommendations are mostly set to a longer centrifugation time at a lower speed to assure sample quality.…”
Section: Centrifugationmentioning
confidence: 99%
“…In Denmark, individual laboratories may choose which combination of official guidelines and local protocols suit their local practices and quality assurance strategies. This autonomy may not be just a Danish phenomenon, as a study showed that only 63 % of European laboratories followed a national guideline regarding the handling and storage of blood samples for coagulation tests [ 3 ]. This autonomy may be a concern if locally developed protocols neither follow official guidelines nor the scientific evidence-based literature - as we previously observed for blood tube order of draw in Denmark [ 4 ].…”
Section: Introductionmentioning
confidence: 99%